Students’ Speaking Skill Trough Storytelling Technique At Smp Negeri 4 Tanjung Morawa - Marta Karina Hutabarat; Yohana Dona Pika Limbong; Madina D (elt, 2021)
Abstract A speaking talent is the ability to say or recite an idea that a person has, and it includes features of pronunciation, vocabulary, and syntax. The objective of speaking is to express a thought or sensation that has arisen in the individual as a result of listening to music or learningcontent. The storytelling technique is one way to help pupils enhance their speaking abilities. Storytelling is a fascinating practice that encourages children to use their imaginations.Storytelling can assist them improve their language abilities while also deepening and broadening their comprehension of the story's characters. A qualitative research design is used in this study. The goal of this study is to help researchers and readers understand what media and approaches teachers use in the classroom to help students, particularly junior high school students, enhance their vocabulary. Keywords : Storytelling, Effect, Speaking skill